Idiopathic laryngeal hematoma,what is the possible cause? - Salman, Amiruddin; Syarifah Najihah, .; Mohd Nor Kamaruzaman, Esa; Khairudin, Abdullah; Amran, Mohamad; Atiqah Farah, Zakaria (2018)
The early manifestations of idiopathic thrombocytic purpura include easy bruising, petechiae, epistaxis, gingival bleeding, conjunctival haemorrhages, and prolonged bleeding from skin injuries. Laryngeal involvement is very rare and only reported in 2 literature previously. Airway management need to be performed at the same time with correction of the bleeding tendencies. We are reporting one case of unexplained laryngeal edema and treated for angioedema which later on turn to be hematoma.